(untitled) - Sarosy, Peg (Oxford, 2006)
In Lecture Ready, students learn and practice a variety of listening, note-taking, and discussion strategies before they watch an actual lecture and participate in an extended class discussion about the ideas in the lecture. Students learn two types of listening strategies: Strategies for independently preparing for each stage of the listening process-before a lecture, during a lecture, and after a lecture; Strategies for recognizing "lecture language" - the discourse markers, speech features, and lexical bundles that lectures across disciplines commonly use to guide students in taking in information.
Keywords: Study skills,Listening,English language; Study and teaching,Foreign speakers